Peacebuilding Strategies and Internal Democracy in Lagos State: A Study of All Progressives Congress (APC), Nigeria - Moshood, Abdul-Wasi Babatunde; Orunbon, Nurudeen Olalekan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This research looked at the connection between the All-Progressive Congress's internal democracy in Lagos State, Nigeria, and peacebuilding techniques. To provide direction for the investigation, two hypotheses (tested at the 0.05 level of significance) were established. All political players in the state were included in the population, which was stratified into senatorial districts to provide a sample size of 289 using correlational and descriptive research techniques. Pearson's Product-Moment Correlation Analysis was used to evaluate the data. The results of the study show that there is a positive, moderate, and significant relationship between peacebuilding strategies and power-sharing arrangements with the All-Progressives Congress in Lagos State (r =.643, ρ < 0.05). Additionally, there is a positive, weak, and significant relationship between peacebuilding strategies and inclusivity and diversity with the All-Progressives Congress in Lagos State (r =.312, ρ < 0.05). The study concludes that power-sharing in Lagos State has become increasingly important due to the diverse nature of its population, which consists of people from different ethnic, religious, and socio-economic backgrounds as well as diversity and inclusivity, as it involves recognizing and celebrating the differences that exist among individuals and communities. It is recommended in the study that the political parties in Lagos State, particularly All Progressives Congress (APC) should endeavour to observe internal democracy so as to give room for transparent party primaries, as this would reduce incidences of replacing candidates, thereby promoting an atmosphere for peaceful coexistence, equity and fairness.